2023
DOI: 10.3389/fvets.2023.1147020
|View full text |Cite
|
Sign up to set email alerts
|

Betaine and nano-emulsified vegetable oil supplementation for improving carcass and meat quality characteristics of broiler chickens under heat stress conditions

Abstract: IntroductionThis research aimed to examine the effects of water-added betaine (BET) and/or nano-emulsified vegetable oil (MAGO) on carcass and meat quality characteristics of broilers raised under thermoneutral (TN) and heat stress (HS) conditions.MethodsOn day 21, 640 birds (Ross 308) were randomly assigned to one of two thermal conditions (thermoneutral 22 ± 1°C and heat stress 32 ± 1°C) each containing four treatment groups: Control, BET, MAGO, and a mixture of both (BETMAGO) in a 2 × 4 factorial arrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Betaine increases energy metabolism enzyme activity and reduces liver fat in hens ( Sun L et al, 2023 ). Betaine-supplemented hens have improved growth rate, feed efficiency, and carcass quality, especially during heat stress or disease outbreaks ( Suliman et al, 2023 ; Sun S et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Betaine increases energy metabolism enzyme activity and reduces liver fat in hens ( Sun L et al, 2023 ). Betaine-supplemented hens have improved growth rate, feed efficiency, and carcass quality, especially during heat stress or disease outbreaks ( Suliman et al, 2023 ; Sun S et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…HS conditions adversely affect glycolytic metabolism, protein synthesis, and fat deposition in broilers, and simultaneously over-produces reactive oxygen species (ROS), thereby impairing the meat quality [29]. Extensive studies have confirmed the deleterious influences of HS on the chicken quality in terms of increased drip loss, cooking loss, and muscle brightness, and reduced pH and redness [30][31][32]. Additionally, HS reduces feed intake, resulting in a shortage of myoglobin and other proteins that regulate meat color, which in turn induces an increase in meat brightness and a lower degree of redness [33].…”
Section: Discussionmentioning
confidence: 99%